Influence of Seed Location in the Fruit Pod of Fluted Pumpkin (Telfairia Occidentalis Hook. F.) and Poultry Wastes on Plant Sex Ratio - Aniekwe, N. L; Mbah, M.C (Review of Catalysts, 2015)
The influence of seed location in the fruit pod of fluted pumpkin and inorganic fertilizers and poultry wastes on the plant sex ratio was investigated in 2009 and 2010 in a randomized complete block design in three replications. In 2009, a mean of 25:75 male: female plants per pod resulted from seeds in the head region producing a ratio of 38:62 male: female plants, the middle, 24:76 and in the tail region, 14:86. In 2010, a mean of 30:70 male: female plants per pod were obtained, 33:67 male: female plants from seeds in the head, 24:76 in the middle and 34:66 in the tail. A total plant sex ratio of 1: 3 per fruit pod occurred in the two trials, while more female plants occurred in middle and tail regions (1:3 or 24:76) than in the head region (1:2 or 35.5: 64.5). Fertilizer sources showed no significant influence on the male: female plant ratio, but on the leaf area. Poultry wastes influenced the highest (78.8 cm2), NPK (15:15:15) 57.3 cm2 and the least 48.4 cm2 from control. Plants in the middle region had the highest leaf area (65.8 cm2), Coefficient of variation for male plants was wide in 2009 (52.3) and in the mean of the years (25.4). Smallholder female farmers can increase their business and income by selecting seeds from the middle and tail locations and by augmenting soil fertility with cheap and affordable poultry wastes.